Acetylcholinesterase Biosensor Based on Gold Nanoparticles/Nitrogen−Doped Vertically Oriented Reduced Graphene Oxide Prepared by Single−Step Electrodeposition. Issue 13 (1st January 2019) - Man, Yi; Guo, Kaiming; Jiang, Bin; Zheng, Jianbin
Abstract : A novel acetylcholinesterase (AChE) biosensor based on gold nanoparticles/nitrogen−doped vertically oriented reduced graphene oxide (AuNPs/NVRGO) film was developed for the detection of organophosphorus pesticides (OPs). The AuNPs/NVRGO film was prepared by single−step electrodeposition of nitrogen−doped reduced graphene oxide (NRGO) in the presence of HAuCl4 . This film resulted in excellent electrochemical response and electron−transfer efficiency because of the synergistic effect of AuNPs with NVRGO. In addition, the AChE biosensor exhibited a strong linear relationship for OPs concentrations ranging from 3.0 × 10 −9 to 3.0 × 10 −15  mol L −1 for malathion and 3.8 × 10 −9 to 3.8 × 10 −15  mol L −1 for methyl parathion. Under optimum conditions, the results displayed high sensitivity of the derived biosensor for monitoring malathion and methyl parathion in water down to detection limits of 3.0 × 10 −16  mol L −1 and 2.3 × 10 −14  mol L −1, respectively. The biosensor also revealed operational stability, satisfactory reproducibility, and good recovery. The proposed approach provides an effective and sensitive means of OPs detection because of its several advantages such as simplicity, low cost, and high accuracy.